Is opening-wedge high tibial osteotomy superior to closing-wedge high tibial osteotomy in treatment of unicompartmental osteoarthritis? A meta-analysis of randomized controlled trials. (December 2018) - Wang, Zhan; Zeng, Yihua; She, Wei; Luo, Xiangli; Cai, Liyang
Abstract: Background: High tibial osteotomy (HTO) is an effective surgical technique that can stop or inhibit progression of knee osteoarthritis (OA) and avoid or postpone the need for knee arthroplasty. This meta-analysis determined whether opening-wedge high tibial osteotomy (OWHTO) was superior to closing-wedge high tibial osteotomy (CWHTO) in treatment of unicompartmental OA. Methods: Databases (PubMed, Embase, Web of Science, Cochrane Library and Google) were searched from the time of their establishment to 1st August 2018 for randomized controlled trials (RCTs) comparing OWHTO and CWHTO in patients with unicompartmental OA. The Cochrane risk of bias tool was used to assess methodological quality. Statistical analysis was performed with Stata 12.0. Results: Nine RCTs (599 participants) were included in this meta-analysis. The pooled results showed that there were no significant differences between OWHTO and CWHTO VAS knee pain scores, HSS knee scores, walking distances or hip-knee-ankle (HKA) angles (P > 0.05). Furthermore, there were no significant differences between the two groups in complication and survival rates (p > 0.05). Nevertheless, there was a significantly greater tibial slope angle in OWHTO patients (P < 0.00001). Conclusion: CWHTO reduced the inclination of the tibial plateau, whereas OWHTO increased the posterior tilt, and these factors should be considered in the specific need of an individual patient when choosing the type of osteotomy. Therefore, we are unable to conclude which method is superior. Highlights: Opening-wedge high tibial osteotomy (OWHTO) and closing-wedge high tibial osteotomy (CWHTO) were two common options for unicompartmental osteoarthritis (OA). Only randomized controlled trials were included. CWHTO reduced the inclination of the tibial plateau. CWHTO increased the posterior tilit.